Comparative Cardiovascular Impact of Early-Onset Type 1 and Type 2 Diabetes and Associated Risk Factors in Pediatric and Adult Patients: Cardiovascular Impact of Diabetes - Shafiq, Umar; Munir, Ussama; Naeem, Muhammad; Rehman, Fazal Ur; Ahmad, Iftikhar; Zafar, Muhammad Adnan (Pakistan Journal of Health Sciences, 2025)
Cardiovascular disease is a leading cause of morbidity and mortality among individuals with diabetes, with early-onset cases posing unique risks. Objective: To evaluate and compare the cardiovascular impact of early-onset type 1 and type 2 diabetes mellitus in paediatric versus adult patients and to identify associated clinical, biochemical, and sociodemographic risk factors in a low-resource Pakistani setting. Methods: This was an observational, comparative, cross-sectional study conducted at the Department of Paediatrics, Quaid-e-Azam Medical College, Bahawalpur, from March 2024 to March 2025. A total of 260 participants were enrolled using non-probability consecutive sampling, comprising 130 diabetic patients (aged 10–40 years) with early-onset diabetes mellitus (diagnosed ≤25 years) and 130 age- and gender-matched healthy controls. Data were collected through structured clinical examination, laboratory investigations (including HbA1c, lipid profile, serum creatinine, urinary albumin-creatinine ratio), electrocardiography, and echocardiography. Statistical analysis was performed using SPSS version 26.0. Results: Diabetic patients demonstrated significantly higher prevalence of left ventricular hypertrophy (36.9% vs. 10.8%; adjusted OR: 5.01; 95% CI: 2.51–9.99; p = 0.0001), CIMT ≥0.9 mm (44.6% vs. 16.2%; OR: 4.49; 95% CI: 2.44–8.26; p = 0.0001), and diastolic dysfunction (24.6% vs. 6.9%; OR: 4.25; 95% CI: 1.83–9.89; p = 0.0003). Significant associations were found between cardiovascular complications and poor glycaemic control (HbA1c ≥7%), LDL ≥100 mg/dL, triglycerides ≥150 mg/dL, low socioeconomic status, and sedentary lifestyle. Conclusion: Early-onset diabetes mellitus is strongly associated with adverse cardiovascular outcomes in young Pakistani patients.